Nutrition transition in 2 lowland Bolivian subsistence populations. Issue 6 (31st October 2018) - Kraft, Thomas S; Stieglitz, Jonathan; Trumble, Benjamin C; Martin, Melanie; Kaplan, Hillard; Gurven, Michael
ABSTRACT: Background: Traditional diets are often credited for the robust cardiometabolic health of subsistence populations. Yet, rural subsistence populations are undergoing nutrition transitions that have been linked to the increase in chronic noncommunicable diseases. Few studies have presented detailed dietary estimates in transitioning populations. Objectives: We aimed to 1 ) characterize and compare dietary profiles of 2 neighboring subsistence populations in Bolivia who vary in market integration and 2 ) identify dietary factors contributing to low cardiovascular disease risk. Design: We used a mixed longitudinal design to estimate nutrient intake via 24-h recall and dietary questionnaires among 1299 Tsimane (aged 30–91 y) and 229 Moseten (aged 30–84 y) men and women. We constructed population-level estimates of energy intake, dietary diversity, and nutrient shortfalls and analyzed dietary changes over time and space using multilevel models. Last, we compared Tsimane and Moseten dietary profiles with those of Americans (NHANES). Results: The Tsimane diet was characterized by high energy (2422–2736 kcal/d), carbohydrate (376–423 g/d), and protein (119–139 g/d) intakes; low fat intake (40–46 g/d); and low dietary diversity relative to the average US diet. Most calories (64%) were derived from complex carbohydrates. Total energy and carbohydrate intake increased significantly during the 5-y study, particularly in villages near market towns. Tsimane consumption of food additives (lard, oil, sugar, salt) increased significantly [sugar (15.8 g ⋅ person −1 ⋅ d −1 ) and oil (4.9 mL ⋅ person −1 ⋅ d −1 )] between 2010 and 2015. The more-acculturated Moseten consumed substantially more sugar (by 343%) and oil (by 535%) than the Tsimane. Conclusions: A high-energy diet rich in complex carbohydrates is associated with low cardiovascular disease risk when coupled with a physically active lifestyle. A transition away from a high-fiber and low-fat, low-salt, and low-processed-sugar diet is a salient health risk for transitioning populations. Evidence of a nutrition transition in Bolivia parallels trends of increasing body fat and body mass index, which suggests that a low prevalence of cardiovascular disease may not persist.